Depression, social support and management preferences among Ghanaian post-stroke patients: a case study - Yarney, Lily; Otinkorang, Joseph Nii; Kofi Agboh, Herman Nuake (Intelektual Pustaka Media Utama, 2025)
Post-stroke depression (PSD) significantly impacts the lives of cerebrovascular accident (CVA) survivors, yet tailored support systems and management preferences remain under-researched, particularly in specific healthcare settings. This study assessed the experience of depressive symptoms among CVA survivors, the support systems available to them, and their preferred management methods at the Ledzokuku-Krowor Municipal Assembly (LEKMA) Hospital in Ghana. Utilizing the descriptive case study design, 50 CVA patients were surveyed using a self-structured questionnaire and the Centre for Epidemiological Studies Depression Scale Revised (CESD R-20). Data were analyzed with Microsoft Excel and STATA version 17. Chi-square test of association was used to measure the severity of depression and specific demographic groups. Results indicated a high prevalence of depression (86%), with 10% experiencing moderate and 76% severe depression. Marital status significantly correlated with post-stroke depression (PSD) severity. Primary support sources included spouses/partners and children, providing various forms of support such as physical assistance, emotional well-being, and financial aid. Preferred management options were pharmacology and psychotherapy, driven by the desire for quick symptom relief and concerns over medication side effects and costs. These findings highlight the critical need for enhanced support systems and responsive management strategies to include depression for CVA survivors.